Upaya Meningkatkan Pemahaman Konsep IPA Siswa Melalui Model Pembelajaran Discovery Learning - Nursa'ban, Eva; Ewisahrani, Ewisahrani; Fathurrahmaniah, Fathurrahmaniah (LPPM Institut Pendidikan Nusantara Global, 2025)
To enhance students' understanding of science concepts, particularly on the topic of the properties of light, the researcher connected students' real-life experiences with natural phenomena, facilitating their reasoning so that scientific concepts could be applied in everyday life. This study aimed to determine whether the discovery learning model could improve students’ conceptual understanding in science. The research was conducted at SDN Inpres Bala with 20 fifth-grade students in the second semester of the 2024–2025 academic year. The research method was classroom action research, consisting of two cycles. The results showed that the use of the discovery learning model significantly improved students’ understanding of science concepts. The pre-cycle observation indicated a 35% level of conceptual understanding, which increased to 60% in cycle I and reached 100% in cycle II, demonstrating active student engagement in learning. Throughout the process, the application of discovery learning enabled students to comprehend the material better. This study implies that the discovery learning model can be recommended as an effective instructional approach to enhance students’ understanding of science concepts and improve learning outcomes.